New approaches to unveil the unknown: oxygen depletion and internal eutrophication in a Baltic lagoon over decades - Schernewski, Gerald; Neumann, Thomas; Piehl, Sarah; von Weber, Mario (Frontiers in Environmental Science, 2025)
Oxygen is a key indicator for assessing the ecological condition of coastal waters, yet current monitoring programs often fail to adequately capture the occurrence and impact of hypoxia, anoxia, and their consequences. In this study, we combine long-term observational data with a 3D ecosystem model and use summer peaks of inorganic phosphorus concentrations as a proxy for anoxic events and subsequent sedimentary phosphorus release. This approach allows us to assess the duration, spatial extent, and ecological impacts of oxygen depletion in the Oder/Szczecin Lagoon, located in the southern Baltic Sea. Mass mortality events of aquatic organisms have been observed in the lagoon, and the model indicates that anoxic conditions frequently occur at a large scale directly above the sediment. However, these events are not captured in standard oxygen measurements, sampling 1 m above the sediment. We suggest a site-specific precautionary value for hypoxia of 8 mg O2/L, when measurements are limited to 1 m above the sediment. Daily and hourly maximum wind speeds can serve as site-specific proxies for oxygen depletion, reflecting changes in water mixing depth and indicating periods of stagnation above the sediment. Altogether hypoxia is still an underestimated problem and modified monitoring and assessment strategies are required and suggested. Anoxic phosphorus release from sediments can result in internal phosphorus loads of up to 1,000 tons per month, significantly exceeding all other external phosphorus inputs to the lagoon. The phosphorus concentration peaks do not permit detailed quantification of these anoxic processes and do not appear to have ecological consequences within the lagoon itself. However, it alters the seasonal pattern of nutrient loading and contributes additional phosphorus to the coastal Baltic Sea during the ecologically critical summer months. Over recent decades, both anoxia and internal eutrophication in the lagoon have shown a declining trend, coinciding with reductions in external nutrient inputs from riverine sources. Consequences on policy implementation and monitoring are discussed.